Does the source of capital affect capital structure? - Michael Faulkender; Mitchell A. Petersen (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2004)
Prior work on leverage implicitly assumes capital availability depends solely on firm characteristics. However, market frictions that make capital structure relevant may be associated with a firm's source of capital. Examining this intuition, we find firms which have access to the public bond markets, as measured by having a debt rating, have significantly more leverage. Although firms with a rating are fundamentally different, these differences do not explain our findings. Even after controlling for firm characteristics which determine observed capital structure, and instrumenting for the possible endogeneity of having a rating, firms with access have 35 percent more debt.
Keywords: 330; Kapitalstruktur; Fremdkapital; Finanzintermediär; Rentenmarkt; USA